Kiat Sukses Belajar di Perguruan Tinggi - Etty Nurbayani (UIN Sultan Aji Muhammad Idris Samarinda, 2010)
Learning is a necessity in human life. Learning is the primary way human adapt in his life. If someone does not learn then he can not survive, and of course will not work successful. Learning is continuous, informal with different settings, through activities and any activity that is practical. This Article discusses how to encourage students to learn more optimally. This article was written based on the author's experience as a student. There are a few things to note for success in learning is how to follow the lectures, independent learning, group learning how to study the book and how to deal with the exam. All that can be successful if the factors that influence success in learning, such as one's environment, learning tools and learning how to consider each student.